EKSISTENSI BADAN AKREDITASI PROVINSI SEKOLAH/MADRASAH (BAP S/M) DALAM MENINGKATKAN MUTU PENDIDIKAN MADRASAH DI PROVINSI SULAWESI TENGGARA - Zulkifli. M. (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2015)
Abstract The focuses of this research are to know the performance of  Provincial Accreditation Board for Schools/Madrasah (BAP S/M) at Southeast Sulawesi province in enhancing  education quality, the picture of madrasah education quality assurance, and the factors supporting and hindering the implementation of madrasah education quality assurance. Data collection technique is using interview and documentation which are processed by qualitative approach. The  result shows that the BAP S/M atSoutheast Sulawesi province has done the planning in counting up and allocation of school/Islamic School accreditation, Announcement of accreditation registration, proposal for accreditation, accreditation set of equipment delivery, instrument of collecting data filling, supporting information,   shipment of accreditation instrument, evaluation of instrumentresult and document audit, feasibility decree, Visitation to school/Islamic school, Validation process and visitation result, verification of validation result and recommendation arranging, result and accreditation recommendation, publishing of accreditation certificate, data reporting and socialization of school accreditation result, and has accredited schools/madrasah during the year of 2006-2014 for 5660 schools/madrasah.They are 5109 schools (90,3%) and 551 madrasah (9.7%). For a picture of madrasah education quality assurance, BAP S/M at Southeast Sulawesi province, as an institution accrediting schools/madrasah, has been implementing the program by mapping schools/madrasah as one of the components in improving schools/madrasah education quality referring to the national standard of education. While, the factors supporting the implementation of accreditation for schools/madrasah are the formation of BAP S/M manager at Southeast Sulawesi province, Accreditation Implementation Unit (UPA) for regency/city, good coordination establishment with the Department of National Education and Department of Religious Affairs, the number of assessors in various levels of education, the availability of an adequate budget from central and local government,while the inhibiting factors are the awareness of madrasah leaders are still low and some of them still do not know that there is an accreditation for madrasah, and madrasah management is still poor.Keyword: BAP S/M, Madrasah Education Quality.AbstrakFokus penelitian adalah bagaimanakah kinerja Badan Akreditasi Propinsi Sekolah/Madrasah (BAP S/M) Provinsi Sulawesi Tenggara dalam meningkatkan mutu pendidikan, dan bagaimanakah potret penjaminan mutu pendidikan Madrasah, serta faktor-faktor apakah yang mendukung dan menghambat pelaksanaan kebijakan penjaminan mutu pendidikan Madrasah?  Teknik pengumpulan data dilakukan dengan wawancara dan dokumentasi yang diolah dengan cara kualitatif. Hasil penelitian menunjukkan bahwa Kinerja BAP S/M Provinsi Sulawesi Tenggara melakukan rencana jumlah dan alokasi akreditasi sekolah/madrasah, pengumuman pendaftaran akreditasi, pengusulan untuk akreditasi., penyampaian perangkat akreditasi, pengisian instrument pengumpulan data dan informasi pendukung, pengiriman isian instrument akreditasi, evaluasi isian instrument dan audit dokumen, penetapan kelayakan, visitasi ke sekolah/madrasah,  validasi proses dan hasil visitasi, verifikasi hasil validasi dan penyusunan rekomendasi, penetapan hasil dan rekomendasi akreditasi, penerbitan sertifikat akreditasi, pelaporan data dan sosialisasi hasil akreditasi sekolah/madrasah, dan telah berhasil mengakreditasi S/M sepanjang tahun 2006-2014 sebanyak 5660 sekolah/madrasah, yakni 5109 sekolah atau90,3% dan 551 madrasah atau 9,7%, dan Potret penjaminan mutu pendidikan, BAP S/M Provinsi Sulawesi Tenggara, sebagai lembaga yang mengakreditasi Sekolah/Madrasah telah melaksanakan programnya dengan memetakan sekolah/madrasah sebagai salah satu komponen peningkatan mutu pendidikan sekolah/madrasah dengan mengacu pada standar nasionalpendidikan. Sedangkan faktor pendukung pelaksanaan akreditasisekolah/madrasah adalah terbentuknya pengurus BAP S/M Provinsi Sulawesi Tenggara, Unit Pelaksana Akreditasi (UPA) Kab/Kota, terjalinnya koordinasi yang baik dengan Diknas dan Depag, asesor yang cukup dalam berbagai jenjang pendidikan, tersedianya anggaran yang memadai dari pemerintah pusat dan daerah, sedangkan factor penghambat adalah kesadaran pimpinan madrasah masih rendah dan masih ada di antaranyayang belum mengetahui adanya akreditasi madrasah, serta lemahnya manajemen madrasah.Kata Kunci: BAP S/M, Mutu Pendidikan Madrasah